2016
DOI: 10.1002/asl.682
|View full text |Cite
|
Sign up to set email alerts
|

A counterexample of aerosol suppressing light rain in Southwest China during 1951–2011

Abstract: Surface meteorological observation data and aerosol optical depth (AOD) data from 1951-2011 were analyzed for Tengchong city, which is a clean city in Southwest China. A significant reduction of light rain, accompanied by an increase of visibility and a decrease of AOD, was observed. Thus, the observed light rain reduction in Tengchong was not associated with an increase of aerosols. The main cause of the reduction in light rain was the decrease of relative humidity in the layer between 850 to 500 hPa, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Thus, this issue should be further studied in the context of climate change, since significant light rain reduction has been observed in many regions, including non‐polluted and polluted regions (Qian et al ., ; Huang and Wen, ). In recent, we have found an example of long‐term light rainfall reduction in a very clean region in Southwest China, which also be interpreted by the change of RH (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this issue should be further studied in the context of climate change, since significant light rain reduction has been observed in many regions, including non‐polluted and polluted regions (Qian et al ., ; Huang and Wen, ). In recent, we have found an example of long‐term light rainfall reduction in a very clean region in Southwest China, which also be interpreted by the change of RH (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Light precipitation is considered an important factor influencing drought control, can directly affect soil moisture content and water conservation, and help to reduce the frequency of drought, especially in arid and semi-arid areas [15]. Jiang et al investigated changes in rainfall intensity from different parts of China and found that light precipitation events have been decreasing across the country in the context of continued warming of the global climate [16].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al investigated changes in rainfall intensity from different parts of China and found that light precipitation events have been decreasing across the country in the context of continued warming of the global climate [16]. The proportion of light precipitation to total precipitation and light precipitation days to total precipitation days increased from southeast to northwest China, and light precipitation days accounted for more than 60% of the total precipitation days [12,15,17]. Additionally, a reduction in the number of light precipitation days was observed in most regions of China [12,18,19], and a lower intensity of light rain was associated with a much more significant reduction in the amount and number of light rain days [14].…”
Section: Introductionmentioning
confidence: 99%
“…In China, a decrease of light-rain days has been observed in many regions as well as in the country as a whole (Huang and Wen, 2013;Li and Su, 2014;Ren et al 2015;Zhou et al, 2020). Change in temperature, aerosol concentrations, cloud, and relative humidity are examined to explain the possible reasons for light precipitation decrease, but no consensus has been reached (Huang and Wen, 2013;Wu et al, 2016. Wen, et al, 2016, though Ren et al (2016) attributed the reduction to a combined in uence of urbanization, aerosols and measurement error.…”
Section: Introductionmentioning
confidence: 99%